2019
DOI: 10.1371/journal.pone.0225329
|View full text |Cite
|
Sign up to set email alerts
|

How medical professional students view older people with dementia: Implications for education and practice

Abstract: BackgroundHealthcare professionals’ attitudes to older people, and especially those living with dementia, may contribute to unsatisfactory healthcare. Despite repeated calls to address increasing need, training an adequate geriatric workforce remains an international concern. Of particular concern are the attitudes and knowledge healthcare workers may hold about people living with dementia. Students’ knowledge of dementia has been found to be low at the beginning of their university education and has shown lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
(59 reference statements)
1
26
0
2
Order By: Relevance
“…Numerous studies have found a lack of knowledge and inappropriate attitudes towards dementia among students in health and non-health areas [16][17][18][19]. In a systematic review, Ahmad et al found that the majority of college and university students reported low understanding of risk factors and causes related to dementia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found a lack of knowledge and inappropriate attitudes towards dementia among students in health and non-health areas [16][17][18][19]. In a systematic review, Ahmad et al found that the majority of college and university students reported low understanding of risk factors and causes related to dementia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Participants expressed preference for approaches which actively involved and empowered them to maximise independence and live well with their condition. There is a plethora of literature to support such approaches [21,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…GPs commonly report that they receive insufficient pre-and post-qualification training in dementia [14,33,[35][36][37][38]. Practitioner age and experience level influence attitudes, awareness, level of confidence and practice intention regarding the timely diagnosis and management of dementia [35,39,40]. Given the reported limitations of dementia-related medical training for students and registrars [35,41], and the essential role of GPs in dementia diagnosis and care particularly for people who may not use specialist services [22], there is urgent need for dementia-related professional development for GPs.…”
Section: Introductionmentioning
confidence: 99%